2018
DOI: 10.1093/jee/toy043
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Diamide Insecticides in Plutella xylostella (Lepidoptera: Plutellidae): Comparison Between Lab-Selected Strains and Field-Collected Populations

Abstract: Diamondback moth, Plutella xylostella (L.; Lepidoptera: Plutellidae), is an important pest of crucifers worldwide. The extensive use of diamide insecticides has led to P. xylostella resistance and this presents a serious threat to vegetable production. We selected chlorantraniliprole (Rf) and flubendiamide (Rh) resistance strains of P. xylostella with resistance ratios of 684.54-fold and 677.25-fold, respectively. The Rf and Rh strains underwent 46 and 36 generations of lab-selection for resistance, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“… a Part of data taken from our previous studies of Qin et al 2018 . b RR(Resistance Ratio) = LD 50 of resistant strain/LD 50 of susceptible strain.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… a Part of data taken from our previous studies of Qin et al 2018 . b RR(Resistance Ratio) = LD 50 of resistant strain/LD 50 of susceptible strain.…”
Section: Methodsmentioning
confidence: 99%
“…The treated larvae named QR c57 , QR c58 , QR c59 , and QR c60 , respectively. And the toxicity of chlorantraniliprole in every generation of QR c and R c strains with 20 larvae was assayed by the topical application according to the previous studies, respectively ( Qin et al 2018 ). The test was replicated three times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed there to be a glycine (G) to glutamic acid (E) mutation (Troczka et al 2012; Troczka et al 2015) at target site 4,946 in highly diamide‐resistant populations of P. xylostella in Thailand and the Philippines, which is located near a transmembrane region of the carboxyl end of receptor gene, highly conserved in all insect ryanodine receptor (RyR) (Gong et al 2014), and is considered the main cause of the resistance of P. xylostella to chlorantraniliprole. In addition, the detoxification metabolism of enzymes, such as cytochrome P450 monooxygenase (P450), carboxylesterase (CarE), and glutathione S‐transferase (GST) (Hu et al 2014; Wang et al 2013), or the amino acid G4946E, E1338D, Q4594L, and I4790M (I4790K) coordinated mutations in RyR (Guo et al 2014; Jourakua et al 2020), or mRNA expression changes of PxRyR and cytochrome P450 CYP6BG1 (Li et al 2015; Li et al 2018; Qin et al 2018; Sun et al 2012; Yan et al 2014) are also important mechanisms by which P. xylostella resists chlorantraniliprole. We found that most of the aforementioned studies elucidate the mechanism of resistance to chlorantraniliprole, but few address the mechanism of resistance to flubendiamide.…”
Section: Introductionmentioning
confidence: 99%
“…Diamides act selectively to activate the insect ryanodine receptor in the endoplasmic reticulum of insects, leading to irreversible muscle contraction, paralysis, and feeding cessations (Nauen, 2006). However, within a short period of time, DBM populations showed resistance, especially to chlorantraniliprole, in many countries including Brazil, China, Korea, USA, Philippines, India, Japan, Vietnam, and Thailand (Troczka et al ., 2012; Wang & Wu, 2012; Ribeiro et al ., 2014; Steinbach et al ., 2015; Nauen & Steinbach, 2016; Qin et al ., 2018). Additionally, in 2012 there were 79 insecticide molecules to which DBM populations had shown resistance (Sun et al ., 2012), whereas this number reached 95 molecules in 2018 (IRAC, 2018) and for this reason DBM is considered the most difficult cruciferous pest to control.…”
Section: Introductionmentioning
confidence: 99%